METHOD OF AUDIT OF FIXED ASSETS AT MOTOR VEHICLE ENTERPRISES - MIKHLIAIEVA, DARIA; BЕLOZERTSEV, VASYL (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article reveals the methodology of the audit at motor transport enterprises of Ukraine. One of the most important parts of the development of Ukraine's productive forces is the transport industry, which provides production and circulation processes, transporting manufactured products to the month of its sale and consumption, as well as providing passenger transportation services. Today, almost every company, regardless of its economic activity, owns its own vehicles. But for trucking companies, cars are the main means of providing services. That is why the issue of effective use of motorsports, which is impossible without a quality audit, is quite relevant. Methods of auditing fixed assets at motor transport enterprises of Ukraine, as well as at other types of enterprises, defined by International Standards on Auditing. In accordance with ISA 200 «Purpose and Basic Principles of Auditing Financial Statements», the purpose of an audit of property, plant and equipment is for the auditor to express an independent professional opinion on the correctness of the entity’s financial statements. The article considers the main tasks of the audit of fixed assets in motor transport enterprises, as well as the main procedures used in the audit of fixed assets. The paper proves the importance and necessity of auditing the accounting of fixed assets at motor transport enterprises, because the effectiveness of their use affects the cost of motor transport services and as a consequence on the financial results of transport enterprises of Ukraine. The article also presents a test of internal control of fixed assets at the trucking company, which should be carried out at the preparatory stage of the audit of fixed assets and provide the auditor with the necessary information to develop an optimal audit program, taking into account the activities of the trucking company. In addition, the article provides samples of working documents of the auditor during the inspection of fixed assets at the trucking company.
Keywords: audit; motor transport enterprise; fixed assets; methodology; audit program; audit plan; working documents of the auditor